Micmac Analysis of Improving Social Variables of Expected Years of Schooling (EYS) in Coastal and Non Coastal Areas in Pasangkayu Regency, West Sulawesi - Harsuko Riniwati; Inaba Inaba; Risya Viantika; Ridwan Danuarta Galisong (Faculty of Fisheries and Marine Science, Brawijaya University, 2023)
The condition of coastal communities, including the Pasangkayu area, in terms of the Expected Years of Schooling (EYS), is still very vulnerable. This study aims to analyze the key factors of increasing the EYS of the community in the coastal countryside of Pasangkayu Regency. The Matrix of Cross Impact Multiplications Applied to a Classification (MICMAC) methods were used in this study. Respondents are experts sourced from the government, educational institutions, non-governmental organizations and communities in the Coastal Village of Pasangkayu Regency. The results showed that the key factor in increasing the EYS in Coastal Village, Pasangkayu Regency was helping parents. The economic condition of coastal rural communities is still vulnerable, so helping people and being able to go to school is a key factor in increasing the EYS. Institutions related to coastal villages are advised to develop work programs that support research results, namely by increasing the old expectations of coastal community schools through these key factors. One way is to develop a school model for fishermen's children. The strategy is carried out by mobilizing teachers to teach non-formal schools for fishermen's children. Supported by the Education Office in equivalence of diplomas with formal education. EYS, can be increased through the increasing number of elderly school-age population who continue to higher education.